RANOLAZINE IN ISCHEMIC HEART DISEASE - V. P. Lupanov (Столичная издательская компания, 2015)
Study results of a new anti-anginal drug (an inhibitor of sodium channels - ranolazine) are presented. Indications, contraindications, major clinical trials of the drug in patients with ischemic heart disease are considered.